Rescuing Nones From the Reference Category: Civic Engagement Among the Nonreligious in America. (April 2018) - Frost, Jacqui; Edgell, Penny
Religious individuals are repeatedly found to be more civically engaged than nonreligious individuals. However, most studies of civic engagement relegate the nonreligious to the reference group; the "Nones" are treated as homogeneous and assumed to have few avenues for civic engagement. We bring the nonreligious out of the reference group and explore how variations in nonreligious identification, belief, and behavior affect civic engagement. We find important variations among the nonreligious in terms of their propensity to be civically engaged that are lost when their heterogeneity is ignored. Those who identify as "nothing in particular" (NIP) are much less likely to show interest or engagement in civic life than are atheists, agnostics, and the "spiritual but not religious, " and we show that the image of the nonreligious as uninvolved in civic life is inaccurate and most likely driven by forms of analysis that disproportionately weight the experiences of the "NIPs."